History of Segara Kembang Village OKU Regency as a Local History Learning Resource for Daarul Aitam High School Palembang - Liza Nadiya; Aan Suriadi; Wandiyo Wandiyo; Muhammad Idris; Ahmad Zamhari (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
Segara Kembang Village is one of the villages located in Lengkiti District, Ogan Komering Ulu (OKU) Regency, South Sumatra Province. The formulation of the problem in this study is how the history of Segara Kembang Village, OKU Regency as a source of local history learning at Daarul Aitam Palembang High School. From this problem, the researcher aims to find out the history of Segara Kembang Village starting from the village kepuyangan, the founders of the village, the state of the village during the Dutch Colonial period, the Japanese colonization until Indonesia's Independence to be used as an addition to the learning process, especially regarding the local history that exists in a region in order to achieve effective and efficient learning, and can add insight and knowledge about the historical value of the village for the people of Segara Kembang Village, OKU Regency. The method used in this research is descriptive qualitative method. The results of the research and discussion show that Segara Kembang Village has its own historical story with the discovery of a lot of evidence so that it can increase knowledge and insight related to the importance of local history in an area in Indonesia. The community and students can also recognize the identity of a region through local history in Segara Kembang Village.